Low Magnitude of Compression Enhances Biosynthesis of Mesenchymal Stem Cells towards Nucleus Pulposus Cells via the TRPV4-Dependent Pathway - Yibo Gan (Stem Cells International, 2018)
Mesenchymal stem cell- (MSC-) based therapy is regarded as a promising tissue engineering strategy to achieve nucleus pulposus (NP) regeneration for the treatment of intervertebral disc degeneration (IDD). However, it is still a challenge to promote the biosynthesis of MSC to meet the requirement of NP regeneration. The purpose of this study was to optimize the compressive magnitude to enhance the extracellular matrix (ECM) deposition towards discogenesis of MSCs. Thus, we constructed a 3D culture model for MSCs to bear different magnitudes of compression for 7 days (5%, 10%, and 20% at the frequency of 1.0 Hz for 8 hours/day) using an intelligent and mechanically active bioreactor. Then, the underlying mechanotransduction mechanism of transient receptor potential vanilloid 4 (TRPV4) was further explored. The MSC-encapsulated hybrids were evaluated by Live/Dead staining, biochemical content assay, real-time PCR, Western blot, histological, and immunohistochemical analysis. The results showed that low-magnitude compression promoted anabolic response where high-magnitude compression induced the catabolic response for the 3D-cultured MSCs. The anabolic effect of low-magnitude compression could be inhibited by inhibiting TRPV4. Meanwhile, the activation of TRPV4 enhanced the biosynthesis analogous to low-magnitude compression. These findings demonstrate that low-magnitude compression promoted the anabolic response of ECM deposition towards discogenesis for the 3D-cultured MSCs and the TRPV4 channel plays a key role on mechanical signal transduction for low-magnitude compressive loading. Further understanding of this mechanism may provide insights into the development of new therapies for MSC-based NP regeneration.